NiO Nanosheets Coupled With CdS Nanorods as 2D/1D Heterojunction for Improved Photocatalytic Hydrogen Evolution - Wei, Lin; Zeng, Deqian; Xie, Zongzhuo; Zeng, Qingru; Zheng, Hongfei; Fujita, Toyohisa; Wei, Yuezhou (Frontiers in Chemistry, 2021)
Designing low-cost, environment friendly, and highly active photocatalysts for water splitting is a promising path toward relieving energy issues. Herein, one-dimensional (1D) cadmium sulfide (CdS) nanorods are uniformly anchored onto two-dimensional (2D) NiO nanosheets to achieve enhanced photocatalytic hydrogen evolution. The optimized 2D/1D NiO/CdS photocatalyst exhibits a remarkable boosted hydrogen generation rate of 1,300 μmol h−1 g−1 under visible light, which is more than eight times higher than that of CdS nanorods. Moreover, the resultant 5% NiO/CdS composite displays excellent stability over four cycles for photocatalytic hydrogen production. The significantly enhanced photocatalytic activity of the 2D/1D NiO/CdS heterojunction can be attributed to the efficient separation of photogenerated charge carriers driven from the formation of p-n NiO/CdS heterojunction. This study paves a new way to develop 2D p-type NiO nanosheets-decorated n-type semiconductor photocatalysts for photocatalytic applications.